The roles of diet, speciation and extinction on the diversification of birds, and on the assembly of frugivory networks - Ferreira, Gustavo Burin (2017)
To understand how diversity varies through time and/or space we need to understand speciation and extinction dynamics, and ultimately which factors (biotic or abiotic) affect such dynamics. It has been argued that biological interactions play an important role on the diversification of organisms, but macroevolutionary studies have usually adopted a simple characterization of species interactions. On the other hand ecological studies usually focus on well-characterized interactions of very few species. A network approach can augment our understanding of the ecological roles played by different species but it still lacks an evolutionary perspective preventing us to fully understand how ecological interactions are assembled. Using the available phylogeny, dietary data for virtually all bird species (approximately 9965 species) and a large collection of frugivory net- works, we tested the effect of diet on the diversification of birds, and the relationship between ecological roles within interaction networks and diversification dynamics of frugivorous species. Lastly, using computational simulations, we assessed the per- formance of two state-of-the-art methods to estimate diversification rates using molecular phylogenies. We suggest that omnivory acts as macroevolutionary sink where its ephemeral nature is retrieved through transitions from other guilds rather than from omnivore speciation. We propose that these dynamics result from competition within and among dietary guilds, influenced by the deep-time availability and predictability of food resources. We also observed that in the temperate zone, lineages with high-paced evolutionary dynamics (e.g. higher turn- over rates) typically do not occupy central roles in frugivory net- works, and that these restrictions are modulated by water avail- ability/predictability. Lastly, we found that the two state-of-the art phylogenetic methods perform equally well in diversity de- cline scenarios when estimating current rates, but both fail to detect the true diversification trajectory when extinction rates vary in time. This dissertation contributes to the understanding of biotic and abiotic mechanisms driving both the diversification and the assembly of interaction networks, and also provides important information on the reliability of diversification rate estimates by current, widely used methods